THE RELATIONS OF STRESS WITH CHANGES OF PATTERN MENSTRUAL CYCLE IN STUDENTS AT STIKES MURNI TEGUH MEDAN - Rostime Hermayerni Simanullang (STIKes Murni Teguh, 2018)
Introduction: The Process of menstruation can pose potential health problems of the female reproductive associated with fertility, namely the interference pattern of menstruation that can occur in some women from industrialized and developing countries. Expected women can cope with stress better so it doesn't affect the menstrual cycle. Objective: To determine the relations between stress with the pattern of the menstrual cycle on the student STIKes Murni Teguh Medan. Methods: this study used the analytical survey method with cross sectional approach. There are thirty-five samples are selected by using the total sampling technique. Chi Square test used to analyze the data in this study. This study done on January 2018. Results: Results of this study showed that Univariate analysis was conducted to determine the description of the respondents according to the variables studied in the form of frequency distribution tables, while the bivariate analysis using chi-square test to see the relationship of the variables studied and obtained a value of p = 0.000 or p <0.005. Conclution: There is a significant correlation between stress with changes in the pattern of the menstrual cycle on the student STIKes Murni Teguh Medan. From the data the level of stress the students need further attention because of the results of the research obtained there are 8 people (22.86%) who experienced severe stress when faced with problems in life. Abstrak Pendahuluan: Proses menstruasi dapat menimbulkan potensi masalah kesehatan reproduksi wanita berhubungan dengan fertilitas yaitu pola menstruasi yang dapat terjadi pada sebagian wanita dari negara industri maupun negara berkembang. Diharapkan wanita dapat mengatasi stress dengan baik sehingga tidak mempengaruhi siklus menstruasi. Tujuan: Untuk mengetahui adanya hubungan antara stress dengan perubahan pola siklus menstruasi pada mahasiswa STIKes Murni Teguh Medan. Metode: penelitian ini menggunakan metode survey analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini meliputi para mahasiswa reguler semester I STIKes Murni Teguh Medan dengan jumlah siswa 35 orang pada Bulan Januari 2018. Pengambilan sampel menggunakan tehnik total sampling. Hasil: Analisis univariat dilakukan untuk mengetahui gambaran responden menurut variable yang diteliti dalam bentuk tabel distribusi frekuensi, sedangkan analisis bivariat menggunakan uji chi-square untuk melihat hubungan variable yang diteliti dan didapat nilai p = 0.000 atau p <0.005. Kesimpulan: Ada hubungan ada yang signifikan antara stres dengan perubahan pola siklus menstruasi pada mahasiswi STIKes Murni Teguh Medan. Dari data tingkat stress mahasiswa perlu perhatian lebih lanjut karena dari hasil penelitan yang didapat ada 8 orang (22.86%) yang mengalami stress berat ketika menghadapi masalah dalam hidup.